Efektivitas Pelatihan Teknologi Budidaya Bawang Putih Varietas Lokal Ramah Lingkungan dengan Metode Ceramah di Kabupaten Karanganyar - Mardiyanto, Tri Cahyo; Prastuti, Tri Reni (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
Garlic (Allium Sativum L.) is a vegetable that has a lot of profit because its high economic value. Garlic consumption from year to year increases with population growth, but this increase has not matched with an increase in production due to many constraints such as pest attack. Training for garlic farmer aims to improve farmers' knowledge in the application of garlic environmentally friendly cultivation technology. Training of farmers was conducted on 14 April 2015 using the lecture method.The purpose of this study was to determine the effectiveness of the training model using the lecture method to garlic farmers in Karanganyar. The samples used were 20 farmers from the garlic farmers in Karanganyar. Purposive sampling was used as sampling technique.The study was conducted by giving pretest and postest to determine the increase farmers' knowledge, then the data were analyzed using non-parametric statistical analysis (Wilcoxon Match Pairs Test). The results showed that the value of the Z count on the Wilcoxon test was -3.106 an absolute value. Furthermore, the error level of 5%, Z table = 1.64 so that the Z count is greater than Z table. This shows that training the farmers by using lecture method in Karanganyar was effective to improve the knowledge of the farmers.